Is the bacterial leaf nodule symbiosis obligate for Psychotria umbellata? The development of a Burkholderia-free host plant - Sinnesael, A.; Leroux, O.; Janssens, S.B.; Smets, E.; Panis, Bartholomeus; Verstraete, B. (Public Library of Science, 2019)
The bacterial leaf nodule symbiosis is an interaction where bacteria are housed in specialised structures in the leaves of their plant host. In the Rubiaceae plant family, host plants interact with Burkholderia bacteria. This interaction might play a role in the host plant defence system. It is unique due to its high specificity; the vertical transmission of the endophyte to the next generation of the host plant; and its supposedly obligatory character. Although previous attempts have been made to investigate this obligatory character by developing Burkholderia-free plants, none have succeeded and nodulating plants were still produced. In order to investigate the obligatory character of this endosymbiosis, our aims were to develop Burkholderia-free Psychotria umbellata plants and to investigate the effect of the absence of the endophytes on the host in a controlled environment.